Sustainable catalytic rearrangement of terpene-derived epoxides: towards bio-based biscarbonyl monomers. (24th July 2020) - Löser, P. S.; Rauthe, P.; Meier, M. A. R.; Llevot, A.
Abstract : Seeking a sustainable and selective approach for terpene modification, a catalyst deconvolution approach was applied to the Meinwald rearrangement of (+)-limonene oxide as a model substrate to yield dihydrocarvone. In order to identify the most suitable catalyst and reaction conditions, different Lewis acids were evaluated. Bismuth triflate proved to be the most active catalyst under mild reaction conditions, with a low catalyst loading (1 mol%) and a relatively short reaction time (3 h). The optimized reaction conditions were subsequently transferred to other terpene-based epoxides, yielding different bio-based biscarbonyl structures, which constitute interesting and valuable substances, e.g. for polymer synthesis or as fragrances. Monoepoxides derived from ( R )-(−)-carvone and (+)-dihydrocarvone rearranged to the desired products with high selectivities and yields. γ-Terpinene dioxide could be transformed in a double rearrangement to the respective biscarbonyl in moderate yields. A better result was achieved for limonene dioxide after further adjustment of the protocol to reach acceptable yields with a low catalyst loading of 0.1 mol% using 2-methyl tetrahydrofuran as a sustainable solvent. Compared to many procedures described in the literature, this procedure represents a step towards an increased sustainability in terpene modification by considering several principles of Green Chemistry, such as renewable resources, catalysis and mild reaction conditions for elementary chemical transformations. This article is part of a discussion meeting issue 'Science to enable the circular economy'.